Beyond Myelination: Possible Roles of the Immune Proteasome in Oligodendroglial Homeostasis and Dysfunction - Madeira, Miguel M.; Hage, Zachary; Tsirka, Stella E. (Frontiers in Neuroscience, 2022)
Oligodendroglia play a critical role in CNS homeostasis by myelinating neuronal axons in their mature stages. Dysfunction in this lineage occurs when early stage OPCs are not able to differentiate to replace dying Mature Myelinating Oligodendrocytes. Many hypotheses exist as to why de- and hypo-myelinating disorders and diseases occur. In this review, we present data to show that oligodendroglia can adopt components of the immune proteasome under inflammatory conditions. The works reviewed further reflect that these immune-component expressing oligodendroglia can in fact function as antigen presenting cells, phagocytosing foreign entities and presenting them via MHC II to activate CD4+ T cells. Additionally, we hypothesize, based on the limited literature, that the adoption of immune components by oligodendroglia may contribute to their stalled differentiation in the context of these disorders and diseases. The present review will underline: (1) Mechanisms of neuroinflammation in diseases associated with Immune Oligodendroglia; (2) the first associations between the immune proteasome and oligodendroglia and the subtle distinctions between these works; (3) the suggested functionality of these cells as it is described by current literature; and (4) the hypothesized consequences on metabolism. In doing so we aim to shed light on this fairly under-explored cell type in hopes that study of their functionality may lead to further mechanistic understanding of hypo- and de-myelinating neuroinflammatory disorders and diseases.